Analisis Faktor – Faktor yang Mempengaruhi Penyusunan Anggaran Pendapatan dan Belanja Daerah Berbasis Kinerja Pada Pemerintah Kabupaten Aceh Singkil - Ismid, Faisal; Kusmanto, Heri; Lubis, MaksumSyahri (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2020)
The problem in this study is whether the commitment of all organizational components, improving the administration system, sufficient resources, rewards and sanctions have a simultaneous and partial effect on the preparation of Performance-based Regional Revenue and Expenditure Budget in Aceh Singkil Regency. Respondents in this study were 92 people from 46 SKPD who were the sum of all heads and sub-districts of Sub-Province of the Regional Work Unit (SKPD) program in the Aceh Singkil district. This study was a quantitative research with multiple regression analysis with non-dependent variables. performance-based budget (Y) and the independent variables are: Organizational commitment (X1), system improvement (X2), sufficient resources (X3), reward (X4), and punishment (X5)From the results of the study, it can be explained that overall (simultaneous) commitment variables from all organizational components, improving the administration system, sufficient resources, awards and sanctions have an effect on the preparation of Performance-based Regional Revenue and Expenditure Budget in Aceh Singkil Regency. Partially the commitment variable from the organizational component has a negative effect and does not significantly influence the preparation of Performance-based Regional Revenue and Expenditure Budget in Aceh Singkil Regency, while other variables that improve the administration system, sufficient resources, rewards and sanctions have a positive and significant effect on the preparation of the Budget Regional Income and Expenditures based on Performance in Aceh Singkil District.